Correction for Ristaino et al., The persistent threat of emerging plant disease pandemics to global food security - Ristaino, J.B.; Anderson, P.K.; Bebber, D.; Brauman, Kate A.; Cunniffe, N.J.; Fedoroff, N.V.; Finegold, C.; Garrett, K.A.; Gilligan, C.A.; Jones, C.; Martin, M.; MacDonald, G.K.; et al. (National Academy of Sciences, 2021)
Correction for “The persistent threat of emerging plant disease pandemics to global food security,” by Jean B. Ristaino, Pamela K. Anderson, Daniel P. Bebber, Kate A. Brauman, Nik J. Cunniffe, Nina V. Fedoroff, Cambria Finegold, Karen A. Garrett, Christopher A. Gilligan, Christopher M. Jones, Michael D. Martin, Graham K. MacDonald, Patricia Neenan, Angela Records, David G. Schmale, Laura Tateosian, and Qingshan Wei, which published May 21, 2021; 10.1073/pnas.2022239118 (Proc. Natl. Acad. Sci. U.S.A. 118, e2022239118). The authors note that Table 1 appeared incorrectly. In the third column, first row, “Panama disease F. odoratissimum (TR4)” should instead appear as “F. oxysporum f. sp. cubense tropical race 4 (TR4).” The corrected table appears below. The online version has been corrected.